Anew Clustering Method to lmprove the Lifetime of Wireless Sensor Network Using Meta- Heuristic Methods (Journal of the College of Basic Education, 2024)
For greater performance, wireless sensor networks must have a longer lifespan. The lifespan of a wireless sensor network is based on how much energy each node consumes. Node energy consumption decreases as network lifespan grows. Because it requires less energy for information to go between nodes, proper clustering and the optimum selection of cluster heads are crucial to extending the network's lifespan. In this study, the K-means cluster method and the bat optimization algorithm were used to identify the optimum cluster head for the aggregation of a wireless sensor network. Based on the results of the simulated work, the K-means method and the bat algorithm together boost the efficiency of the wireless sensor system.